FV 19 Tracking complexity and causality during cortical reorganization and motor recovery after stroke. (May 2022) - Tscherpel, C.; Mustin, M.; Ziemann, U.; Fink, G.R.; Grefkes, C.
Abstract : I: Combined TMS and EEG represents a non-invasive approach that informs about the local neural state as well as signal propagation within the functional network. Particularly, it has proven powerful at an individual level. In the context of stroke, the individual understanding of the neural mechanisms of reorganization that underlie recovery of function would, in consequence, enable the optimization of rehabilitation strategies including non-invasive neuromodulation. Again, in the context of stroke, TMS-EEG has recently not only revealed the occurrence of the phenomenon of local sleep-like slow waves in conscious awake stroke patients, but has also put these in association to the level of motor deficits and, crucially, the potential of neurological recovery in the chronic phase after stroke. However, a profound mechanistic understanding of the causal underpinnings of stroke recovery and a systematic link from the presence of sleep-like waves after stroke to their behavioral consequences require longitudinal measurements paralleled by clinical assessments. We, therefore, applied the method of TMS-EEG in a cohort of stroke patients in the first two weeks post-stroke, and followed both the course of functional recovery and the development of alterations of TMS-EEG responses through motor reorganization to the chronic stage. M: TMS over ipsilesional M1 combined with EEG in 40 patients with unilateral mild to severe motor deficits due to first-ever ischemic stroke was acquired in the first two weeks after stroke. 35 patients could be re-assessed behaviorally and 28 patients also participated in the TMS-EEG experiments in the chronic phase. TMS-evoked EEG activity of ipsilesional M1 was quantified by spectral and phase domain analysis yielding (i) the occurrence of TMS-evoked slow waves, (ii) cortical off-periods, i.e. high frequency suppression of EEG power, and (iii) local causal interactions quantified by means of phase-locking factor (PLF). Moreover, (iv) alterations of complex global interactions were indexed by the Perturbational Complexity Index (PCI). R: We demonstrated that the slow wave response locally evoked by the perturbation of ipsilesional M1 is associated with a cortical off-period and underpinned by a loss of global signal complexity and a rapid disruption of causal effects in the first weeks post-stroke. However, tracking these signal alterations in combination to the course of motor recovery during the reorganization after stroke revealed that sleep-like waves, independent on the degree of recovery, disappeared in the chronic stage, though their occurrence in the acute stage post-stroke is an indicator for a subsequent poor functional recovery. C: By linking slow waves and the deterioration of global brain dynamics to recovery after stroke, our findings not only link stroke to cortical bistability, a neuronal mechanism precisely characterized in NREM sleep, but put it in a behaviorally and clinically meaningful perspective.